THE ROLE OF IMMIGRATION DETENTION CENTERS IN THE PROTECTION OF THE HUMAN RIGHTS OF ASYLUM SEEKERS - Andreas Agustinus Simamora; Surya Pranata (Polteknik Imigrasi, 2020)
The mobility of foreigners in Indonesia is very numerous and varied. One of them is an asylum seeker who entered Indonesia without immigration documents. In handling immigration violations and to accommodate the asylum seekers, an Immigration Detention Center was formed to provide them with the fulfillment of human rights. This study aims to identify and analyze the Semarang Immigration Detention Center in fulfilling human rights for asylum seekers and to identify and analyze the supporting and inhibiting factors faced. This type of research uses sociological juridical and data analysis using a qualitative approach method. The research data were obtained through interviews and documentation. Meanwhile, the data processing is done through data collection, data presentation, data analysis, and conclusions. The Semarang Immigration Detention Center itself in fulfilling human rights for asylum seekers is carried out by providing structured programs, namely health check services, providing food needs and providing access to education for asylum seekers. Supporting factors are the Semarang Immigration Detention Center in collaboration with related parties, namely PKBI and the Hospital to provide human rights fulfillment for asylum seekers and the enthusiasm of asylum seekers who always participate in the programs and activities given. The inhibiting factors are the absence of medical personnel who are on standby 24 hours, the unavailability of a warehouse for storing medicines, and the language used in communication as well as the different tastes of the food menu for each detainee there.